High-impact interview questions : 701 behavior-based questions to find the right person for every job - Hoevemeyer, Victoria A. (American Management Association, 2006)
"High-Impact Interview Questions saves you both time and effort. The book contains 701 questions you'll be able to use or adapt for your own needs, matched to 62 in-demand skills such as customer focus, motivation, initiative, adaptability, teamwork, and more. It allows you to move immediately to the particular skills you want to measure, and quickly find just the right tough but necessary questions to ask during an interview"--Provided by publisher